Genetic Polymorphisms and Platinum-Based Chemotherapy-Induced Toxicities in Patients With Lung Cancer: A Systematic Review and Meta-Analysis - Liu, Wenhui; Wang, Ying; Luo, Jianquan; Yuan, Haiyan; Luo, Zhiying (Frontiers in Oncology, 2020)
Background: Platinum-based agents, including cisplatin, carboplatin, and oxaliplatin, are indispensable for the treatment of lung cancer. The development of toxicity frequently necessitates dose reduction or discontinuation of therapy, despite the clinical response. Pharmacogenomics studies were reviewed to identify the possible genetic variants that underlie individual susceptibility to platinum-related toxicities. Method: We conducted a systematic search in PubMed and Embase for pharmacogenomics reports that focused on commonly reported platinum-induced toxicities, such as gastrointestinal (GI), hematological, neurological, and other toxicities, in patients diagnosed with lung cancer. Meta-analyses were conducted to determine the association between genetic polymorphisms and platinum-induced toxicity by checking the odds ratio (OR) and 95% confidence interval (CI) using random or fixed-effects models as appropriate. Results: Twenty eligible studies that met the inclusion criteria with sufficient data were extracted and presented comprehensively. A total of 16 polymorphisms from 11 genes were included in the meta-analysis. MTHFR rs1801131 and MDM2 rs1690924 were significantly correlated with platinum-induced GI toxicity (P = 0.04 and P = 0.02, respectively). Patients with the MTHFR rs1801131AA and MDM2 rs1690924TC/CC genotype tended to have a higher risk of GI toxicity than patients with other genotypes did (OR = 1.73, 95% CI = 0.86–2.18; and OR = 0.51, 95% CI = 0.29–0.88, respectively). Compared to carriers of the MTHFR rs1801133CC genotype, carriers of the CT/TT genotype had a significantly increased risk of hematological toxicity (P = 0.01, OR = 1.68, 95% CI = 1.12–2.52). Conclusion: In the future, physicians should pay careful attention to MTHFR and MDM2 for personalized chemotherapy treatment among patients with lung cancer.